Estudo do efeito do gel de alecrim pimenta (lippia sidoides) roeira (myracrodruon urundeuva) e seus princípios ativos isolados na doença periodontal experimental - Soares, Marco Antonio Botelho (2007)
Periodontitis is a chronic inflammatory disease in which alveolar bone resorption and cementum associated with collagen fibers destruction are important events. It configures as a serious problem of public health in the world, being an important risk factor for cardiovascular diseases and to teeth loss in adults. Bacteria and host factors are necessary to the development of this pathology. The natural products can constitute a new alternative of treatment, being described to be effective as a natural mouthrinse by our research group. The objective of the present study was to investigate the mechanisms involved on the effect of gels based on natural products and its derivatives in the experimental periodontal disease (EPD): gel elaborated from the essential oil of Alecrim pimenta 0.5% (GAl) (Lippia sidoides), associated (GAA) or not to the gel of the extract of the Aroeira 5% (GAr) (Myracrodruon urundeuva); gel elaborated from carvacrol 300µg/g (GCa), associate (GCC) or not to the gel of Dimeric Chalcones 600µg/g (GCh); comparing its effects with the doxycycline, used as positive control (GDX). Periodontitis was induced by a nylon thread ligature surgically placed around the cervix of the second left maxillary molars of male Wistar rats. Animals were treated with locally applied gels in the gingival region immediately after the EPD induction three times a day during 11 days. The parameters analysed were alveolar bone loss, histopathologic and microbiological analysis, myeloperoxidase (MPO); levels of TNF-α and IL-1β (by ELISA) and body mass variation. GAA and GCC reduced the alveolar bone loss similar to GDX. Histopatologically, the periodontium of animals treated with GAA and GCC showed preservation of alveolar bone, cementum and collagen fibers of periodontal ligament and reduced neutrophilic and mononuclear cell infiltrate. The effect on neutrophilic infiltrate was confirmed by MPO. There was a significant reduction of TNF-α and IL-1β levels in the group treated with GAA compared to the vehicle group. All natural gels inhibited the growth of bacteria involved in periodontitis and were able to increased body mass compared to vehicle group. These results support clinical trials of these phytochemicals in the treatment of periodontal disease